2015
DOI: 10.1007/s10479-015-1816-6
|View full text |Cite
|
Sign up to set email alerts
|

Capacitated lot sizing problems with inventory bounds

Abstract: In recent years, the capacitated center problems have attracted a lot of research interest. Given a set of vertices V , we want to find a subset of vertices S, called centers, such that the maximum cluster radius is minimized. Moreover, each center in S should satisfy some capacity constraint, which could be an upper or lower bound on the number of vertices it can serve. Capacitated k-center problems with one-sided bounds (upper or lower) have been well studied in previous work, and a constant factor approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The natural extension of the single-item ELSPBI also considering the bounds on the production and replenishment quantity at each period has been addressed recently by Akbalik et al [25]. Concretely, for the single-item CLSP-IB with a constant production capacity, time-dependent inventory bounds and concave costs, the authors showed that the problem could be solved in time O T 4 .…”
Section: Referencementioning
confidence: 99%
“…The natural extension of the single-item ELSPBI also considering the bounds on the production and replenishment quantity at each period has been addressed recently by Akbalik et al [25]. Concretely, for the single-item CLSP-IB with a constant production capacity, time-dependent inventory bounds and concave costs, the authors showed that the problem could be solved in time O T 4 .…”
Section: Referencementioning
confidence: 99%
“…Constraints (5) and (13) are respectively the classical inventory balance equations and capacity constraints. Constraints (14) relate production variables and batch variables while Constraints (15) and (16)…”
Section: Minimizementioning
confidence: 99%
“…It is noticeable, however, that most of the works related to storage capacities are very recent when compared to those considering production capacities (Bitran & Yanasse, 1982;Trigeiro, Thomas, & McClain, 1989;Buschkühl, Sahling, Helber, & Tempelmeier, 2010;Vincent, Duhamel, Ren, & Tchernev, 2020;Tavaghof-Gigloo & Min-ner, 2020). Akbalik, Penz, and Rapine (2015a) study capacitated lot-sizing problems with storage capacities. The authors propose polynomial-time algorithms for the single-item variant of the problem and show NPhardness results for the multi-item variation.…”
Section: Introductionmentioning
confidence: 99%